Effectiveness of internal control: the influence of board and audit committee effectiveness / Ros Amalina Zakaria - Zakaria, Ros Amalina (2013)
Strengthening corporate governance is not the only thing that should be focused on to reduce the risk of corporate collapses. Increasing the effectiveness of internal control also should be given the same consideration. However, factors that may influence the effectiveness of internal control were never been discussed in details, and therefore, the main objective of this study is to examine influence of board and audit committee effectiveness on effectiveness of internal control. Annual reports of top 133 public listed companies are examined by using content analysis for the year of 2011. Various statistical analyses were conducted to examine the effect of board and audit committee effectiveness on the effectiveness of internal control. The results reveal that board of directors' independence and meeting frequency has significant positive influence on the effectiveness of internal control. This implies that companies' internal control is effective when the board of directors is independence and when the board's meeting is conducted more frequently. The results also provide that audit committee's independence has significant negative influence on the effectiveness of internal control, which implies that companies' internal control is less effective when the audit committee is independence. Other determinants of board' and audit committee's effectiveness such as CEO duality, audit committee's size and audit committee's meeting frequency do not give any influences on the internal control effectiveness of Malaysian companies.